Near-infrared and optical emission of WASP-5 b - Kovacs, Geza; Dékány, István; Karamiqucham, B.; Chen, G.; Zhou, G.; Rabus, M.; Kovács, T. (Astronomy and astrophysics, 2022)
Context. Thermal emission from extrasolar planets makes it possible to study important physical processes in their atmospheres and derive more precise orbital elements. Aims. By using new near-infrared (NIR) and optical data, we examine how these data constrain the orbital eccentricity and the thermal properties of the planet atmosphere. Methods. The full light curves acquired by the TESS satellite from two sectors are used to put an upper limit on the amplitude of the phase variation of the planet and estimate the occultation depth. Two previously published observations and one followup observation (published herein) in the 2MASS K (Ks) band are employed to derive a more precise occultation light curve in this NIR waveband. Results. The merged occultation light curve in the Ks band comprises 4515 data points. The data confirm the results of the earlier eccentricity estimates, suggesting a circular orbit of: e = 0.005 ± 0.015. The high value of the flux depression of (2.70 ± 0.14) ppt in the Ks band excludes simple black body emission at the 10σ level and also disagrees with current atmospheric models at the (4-7)σ level. From analysis of the TESS data, in the visual band we find tentative evidence for a near-noise-level detection of the secondary eclipse, and place constraints on the associated amplitude of the phase variation of the planet. A formal box fit yields an occultation depth of (0.157 ± 0.056) ppt. This implies a relatively high geometric albedo of Ag = 0.43 ± 0.15 for fully efficient atmospheric circulation and Ag = 0.29 ± 0.15 for no circulation at all. No preference can be seen for either the oxygen-enhanced or the carbon-enhanced atmosphere models.